ANALYZING FACTORS INFLUENCING INDONESIAN MOBILE GAMERS ON REPURCHASE INTENTION IN FREEMIUM MOBILE GAME WITH PERVAL - Puspa Maharatie, Andhiny
n 2018, Indonesia’s players spent a total of $1.1 billion on games in 2018, making it one of the biggest games markets in Southeast Asia. The rapid growth of mobile and internet users in Southeast Asia attracted many game developers’ attention to develop their products at SEA. The increased use of smartphones in SEA reflects the region’s mobile game market that offers revenue of $ 2.6 billion in 2019, with year-on-year growth of + 17.4%. This makes the world’s fastest-growing region for online game revenue. Mobile is growing the fastest, with the share of game revenue growing from 67,3% in 2018 to 69,4% in 2019. It means that the mobile-focused game publishers are dominating the SEA’s game market. The high-potential growth region was making companies both overseas and local contesting for a piece of it. The competition among game publishers in Indonesia dominated by international game publishers makes it very competitive and challenging for local game publishers to compete. It is found that the total spent of Indonesian players 99% goes to international competitions for all platforms ranging from mobile to PC to console, while 1.2% goes to locally-made games. Based on the problem, this research aims to analyze factors influencing consumers’ repurchase intention to buy virtual items at Mobile Legends by utilizing PERVAL. This research will propose some recommendations for local game publishers and contribute to growing academic literature by adding new variables; satisfaction, user loyalty, and addiction. There are several theories related to this research, including Consumer Behavior, Consumer Behavior towards Mobile Commerce, and PERVAL Framework. The author utilized the PERVAL Framework because it showed that perceived value is a strong indicator of consumer behavior, decision-making processes, and a competitive advantage for a product and service. Also, empirical studies are rare in assessing PERVAL concerning online game players’ attitudes, intentions, and behavioral intentions. To create novelties, the author modified the original PERVAL Framework based on the research’s needs. Furthermore, based on the literature review, the author proposed a model and hypotheses. In terms of research methodology, this research used a quantitative method by utilizing a questionnaire to gather the data by using Google Forms. The author adopted and modified the questionnaire items from previous studies and conducted validity and reliability tests using SPSS 26. The results revealed that all the items are valid and reliable. The author used a Cochran Formula to determine the sample amount, which is at least 385. ii